Bagaimana Loyalitas Pelanggan Pengguna Pertamini di Kota Jambi? - Raja Penungkunen Surbakti; Tona Aurora Lubis; Sigit Indrawaijaya (Universitas Batanghari, 2023)
This study aims to determine and analyze Brand image as Moderating Purchase Decision and Customer Satisfaction on Customer Loyalty of Pertamini Users in Jambi City. This study has a population of all people in Jambi City who have purchased motor vehicle fuel at least once at Pertamini. The analysis tool used in this research is SMART PLS. This study provides the following conclusions: The projected increase in purchasing decisions by product, price and location will increase customer loyalty which is reflected through recommendations, repetition and purchases between lines. Customer satisfaction is projected by service quality, emotional factors can increase customer loyalty which is reflected by recommendations, repetition and purchases between lines. Brand image which is described through recognition, reputation, user image and product image is not able to strengthen or weaken the influence of purchasing decisions projected by product, price and location instead of customer loyalty which is reflected by recommendations, repetition and inter-line purchases. Brand image which is described through recognition, reputation, user image and product image is able to weaken the influence of customer satisfaction which is projected by service quality and emotional factors so as to increase customer loyalty which is reflected through recommendations, repeat purchases and between lines.